2023
DOI: 10.3390/jfb14060320
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Electrets: Recent Advance and Future Perspectives

Abstract: Recently, electrical stimulation, as a non-pharmacological physical stimulus, has been widely exploited in biomedical and clinical applications due to its ability to significantly enhance cell proliferation and differentiation. As a kind of dielectric material with permanent polarization characteristics, electrets have demonstrated tremendous potential in this field owing to their merits of low cost, stable performance, and excellent biocompatibility. This review provides a comprehensive summary of the recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 162 publications
0
22
0
Order By: Relevance
“…Beyond the stifling effects of peritumoral edema on the efficacy of AEF, the edema has other clinically-relevant implications including promoting GBM cell infiltration (Ohmura et al 2023), which has been found to be associated with GBM recurrence/progression (Qin et al 2021). Electrets are inorganic or macromolecular permanently-polarized agents that can provide endogenous electrical stimulation upon application of an external electric field (Grier 2001, Zhang et al 2023, and future pre-clinical research may consider using electrets to modify the electrical properties (e.g. conductivity) of the peritumoral edema in order to improve the efficacy of AEF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the stifling effects of peritumoral edema on the efficacy of AEF, the edema has other clinically-relevant implications including promoting GBM cell infiltration (Ohmura et al 2023), which has been found to be associated with GBM recurrence/progression (Qin et al 2021). Electrets are inorganic or macromolecular permanently-polarized agents that can provide endogenous electrical stimulation upon application of an external electric field (Grier 2001, Zhang et al 2023, and future pre-clinical research may consider using electrets to modify the electrical properties (e.g. conductivity) of the peritumoral edema in order to improve the efficacy of AEF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were gathered and broken down in RIPA buffer (on ice, 30 min), and total proteins were extracted from the cell or tissue lysates via centrifugation (4 °C, 12000× g , 20 min). The proteins extracted were separated using a 10% sodium dodecyl sulfate-polyacrylamide gel and then transferred to a PVDF membrane, a semi-crystalline and non-reactive thermoplastic polymer with excellent piezoelectric properties [ 18 ]. The membrane was incubated with rabbit monoclonal primary antibodies against p-p53 (1:1000) (ab33889, Abcam, USA), p53 (1:1000) (ab32389, Abcam, USA), SLC7A11 (ab175186) and GPX4 (ab125066) at 4 °C overnight.…”
Section: Elisamentioning
confidence: 99%
“…[ 1,2 ] The healing of wounds consists of different stages such as hemostasis, inflammation, proliferation, and remodeling. [ 3,4 ] Massive bleeding from wounds often poses a serious threat to health, and if not treated promptly, it may lead to death. [ 5,6 ] Some chronic injuries have drawbacks such as prolonged inflammation, persistent infection, and insufficient angiogenesis.…”
Section: Introductionmentioning
confidence: 99%